2007
DOI: 10.1080/14034940701271890
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of prevention: An interactive computer-tailored program

Abstract: Participants' responses support previous research findings, advocating a concept of autonomy in terms of positive freedom, through support by others. The promotion of the client's self-understanding and self-development is central in this concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…A common concern across disciplines such as public health and philosophy, is the tension and balance between ensuring the safety of people and respecting their right to autonomy (64,99). As the findings show, communication strategy should be tailored to the culture, values and context, and therefore one may argue that an autonomy-supportive healthcare culture may not "work" in some cultures or countries and that without external regulation (e.g., enforceable legislation), the adherence might be low.…”
Section: Discussionmentioning
confidence: 99%
“…A common concern across disciplines such as public health and philosophy, is the tension and balance between ensuring the safety of people and respecting their right to autonomy (64,99). As the findings show, communication strategy should be tailored to the culture, values and context, and therefore one may argue that an autonomy-supportive healthcare culture may not "work" in some cultures or countries and that without external regulation (e.g., enforceable legislation), the adherence might be low.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to respect the wishes and psychological characteristics of PWS patients, so as to help them feel satisfied, bestow a sense of pride, and achieve the desired goals [2830]. It has been reported that the medical staff should sensitively respond to the patient's behavior modification, rejoice with them, and praise them and that repeating this cycle can encourage the habit of behavior, resulting in treatment efficacy [7, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Autonomy, like privacy, is another theme that is widely addressed but has specific relevance in health and healthcare. A common concern—across disciplines such as medicine, philosophy, and robotics and engineering—is the tension between ensuring the safety of patients, possibly through interventions, and respecting their right to autonomy (Bennett et al 2017 ; Mahoney et al 2007 ; Margot-Cattin and Nygård 2009 ; Sharkey and Sharkey 2012 ; Van Hooren et al 2007 ). However, several articles also warn against the blanket prescription of decontextualized ethical concepts or principles in lieu of a careful examination of how the nature of certain illnesses alter their application.…”
Section: Social Domains: a Review Of Key Issuesmentioning
confidence: 99%
“…maximising engagement) (see Burr et al 2018 for a discussion). Unsurprisingly, therefore, the ethical issues related to autonomy are discussed across a wide-range of records, spanning fields such as psychology, philosophy, public health, and design studies (Calvo and Peters 2013;Desmet and Pohlmeyer 2013;Hart 2016;Lehavot et al 2012;Rughiniş et al 2015;Taddeo 2014;Vallor 2010;Van Hooren et al 2007). However, the approaches taken to autonomy differ widely, suggesting that particular aspects of the concept are only perspicuous when considering specific implementations of digital technology (e.g., an assistive technology for home care).…”
Section: Autonomy and Self-determinationmentioning
confidence: 99%